Genealogi Riddah: dari Masalah Aqidah Menjadi Hudud - Imroatul Azizah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
The problem of riddah is initially only a theological problem, its responsibility only to God, so there was no world sanction. Historically, the Prophet never punished the apostate. But in a classical jurisprudence apostasy is categorisedas Hudu>dand punished with death penalty.Riddah became known after the rebellion of dissidents by Abu Bakr(huru>b al-riddah). This Abu Bakr’s decision and assertiveness be primary for the fuqaha to execute the perpetrators of the riddah. Ulama categorized Riddah be three Classification: First, Riddah engenders serious theological and sociological consequences. Riddah raises the concept of